PENINGKATAN PENYESUAIAN DIRI SISWA MELALUI LAYANAN INFORMASI - Desneli, Desneli; Firman, Firman; Sano, Afrizal (Jurnal EDUCATIO: Jurnal Pendidikan Indonesia, 2016)
Adaptability is essential for the student, because influence friends and social environment determine its succes. The fact that found in Junior High School 1 Padang Panjang discovered a less harmonious relationship of students with one class in learning. The research aims to uncover how the adaptability of the students before and after the given information services. This research using the method of experiment with the types of the one group pretest-posttest design. Population research is grade VII in Junior Hihg School 1 Padang Panjang the length of 261 student with a total samples of 34 students. The data collected using  the  question  form.  Data  analysis  techniques  using  two  different  test average of samples that are related (paired sample t-tests) by using the help program Statistical Product and Service Solution (SPSS) version 17.0. Research findings  show  there  is  a  difference  of  adaptability  of  students  Junior  Hihg School 1 Padang Panjng, before the give information services received an average score of 123,382. Adaptability of students after being given information services increased by average score of 127,735.